1998
DOI: 10.1111/j.1399-0039.1998.tb02978.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor gene polymorphisms in ankylosing spondyiitis

Abstract: Despite the strength of the association of ankylosing spondylitis (AS) with HLA-BZ7, other genetic elements could play a possible role in the pathophysiology of AS. In view of its gene location, in the proximity of the HLA-B locus, and biological effects, tumor necrosis factor genes are potential candidates for additive susceptibility factors to AS. TNFa and TNFP genotypes were analyzed by PCR-RFLP in 57 patients with AS, 102 random controls and 30 HLA-B*27-positive controls. No significant differences of TNFa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…unrelated healthy controls (P \ 0.03). In contrast, other studies from three different European populations demonstrated that polymorphisms at positions -308, -238, and -376 of the TNF-a gene had no effect on susceptibility to AS [15][16][17]. Among these studies, Kaijzel et al identified a significant difference in the -238A allele between HLA-B27 ?…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…unrelated healthy controls (P \ 0.03). In contrast, other studies from three different European populations demonstrated that polymorphisms at positions -308, -238, and -376 of the TNF-a gene had no effect on susceptibility to AS [15][16][17]. Among these studies, Kaijzel et al identified a significant difference in the -238A allele between HLA-B27 ?…”
Section: Discussionmentioning
confidence: 77%
“…AS patients classified by clinical subtypes and controls, n the pathogenesis of AS [11,12]. Several studies have attempted to investigate the relationship between susceptibility to AS and TNF-a polymorphisms in patients with AS [13][14][15][16][17][18][19]. However, the results of these studies are inconsistent, most likely due to the use of diverse study populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF␣-1031 TT 83 59 33 58 29 71 72 56 CT 50 35 22 39 11 27 52 41 C C 8 6 2 3 1 2 4 3 TNF␣-857 CC 122 85 47 84 35 90 106 82 CT 21 14 9 16 4 10 23 18 T T 1 1 0 0 0 0 0 Several studies have identified all nine polymorphisms in the TNF-␣ promoter region, some of which proved to have a functional effect on the transcription of the gene and TNF-␣ mRNA transcription [17,20 -22]. Several association studies link TNF-␣ polymorphism in the promoter region to various infectious and autoimmune diseases [23][24][25][26][27][28][29]. A functional analysis indicated that the 308/376 region is of no functional relevance to TNF transcription [30].…”
Section: Discussionmentioning
confidence: 98%
“…One report detected an association between -308 and AS [126]. No association was found among four promoter polymorphisms (located at c.-244, c.-376, c.-238 and c.-308) between AS and controls [127,128]. The CD-associated promoter polymorphisms have not been tested in SpA.…”
Section: N O T F O R D I S T R I B U T I O Nmentioning
confidence: 99%